A production process of prestressed nonmetallic sound barrier unit plate

CN122975852APending Publication Date: 2026-10-27JIANGSU JINYANG TRAFFIC ENG
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202611167025.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-03
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0004]为了解决现有技术存在的“吸声材料与立柱本体之间出现界面剥离或脱落,立柱翼缘部位易产生拉应力裂缝”的问题,本发明提供一种预应力非金属声屏障单元板生产工艺,利用硅烷偶联剂作为“分子桥”,其一端通过水解、缩合反应与吸声材料表面的硅羟基形成牢固的Si-O-Si共价键;另一端通过其有机官能团(如氨基、环氧基)与RPC基体中的活性组分(如C-S-H凝胶)反应

Benefits of technology

本发明通过将水泥、矿粉、硫铝酸钙膨胀剂、减缩剂和高吸水性聚合物按特定配比混合制备活性粉末混凝土,高吸水性聚合物在低水胶比体系中储存并缓释水分,为硫铝酸钙膨胀剂的水化提供充足水源,使硫铝酸钙膨胀剂在水养过程中持续生成钙矾石并产生体积膨胀,受模具外部约束和无机纤维内部骨架的共同限制,该膨胀被有效转化为活性粉末混凝土内部的化学预应力,从根源上抵消了RPC硬化及服役过程中因自收缩、干燥收缩及荷载产生的拉应力,防止立柱翼缘部位开裂;与此同时,吸声材料表面经硅烷偶联剂接枝的活性基团,在水养环境下与RPC基体中的活性组分发生缩合反应,形成以Si-O-Si共价键为核心的三维化学交联网络,减少了界面剥离问题,从而显著降低开裂风险,提高了抗折强度和抗冲击韧性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122975852A_ABST
    Figure CN122975852A_ABST
Patent Text Reader

Abstract

The application provides a prestressed nonmetal sound barrier unit plate production process, which comprises the following steps: S1, 100 parts of cement, 15-25 parts of mineral powder, 12-15 parts of calcium sulphoaluminate expansive agent, 0.5-1.5 parts of shrinkage reducing agent and 0.15-0.30 parts of superabsorbent polymer are mixed and dry-mixed according to weight parts, then 22-25 parts of water is added and wet-mixed, finally 250-300 parts of inorganic fiber is added and stirred to obtain active powder concrete; S2, the inorganic nonmetal sound-absorbing material is soaked in a silane coupling agent solution, and after being taken out, is dried to obtain a surface-activated sound-absorbing material; S3, the surface-activated sound-absorbing material is placed on the corresponding position of the flange of the side of the column facing the sound source, and is press-formed to obtain a sound-absorbing layer; S4, the active powder concrete is cast and formed in a mold above the sound-absorbing layer, the mold is removed, and then the test piece is immersed in water for curing. The hydration expansion of the CSA expansive agent is converted into chemical prestress under constraint, and the chemical prestress actively offsets the tensile stress caused by shrinkage and load from the inside.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of sound barrier manufacturing technology, and in particular to a manufacturing process for prestressed non-metallic sound barrier unit panels. Background Technology

[0002] Noise barriers are engineering facilities installed along railways and highways to reduce the impact of traffic noise on the surrounding environment. Currently, high-speed railway noise barriers in my country are mainly of the insert type, which requires H-shaped steel columns for support. Existing technologies include the use of Reactive Powder Concrete (RPC) to construct the noise barrier columns. RPC is a new type of cement-based composite material with high strength, high toughness, high durability, and good volume stability. For example, Chinese invention patent CN104775369A discloses a noise barrier column, comprising a column body made of reactive powder concrete and a sound-absorbing material composited on the flange facing the sound source. The column body has an H-shaped cross-section, and the reactive powder concrete includes cement, mineral powder, rice husk ash, natural sand, quartz powder, polycarboxylate superplasticizer, steel fiber, and water. This solution uses non-metallic materials to construct the column body, eliminating corrosion, aging, and bolt loosening issues. Its service life is equal to or even longer than the main structure, requiring no maintenance during use. In addition, non-metallic reinforcing ribs such as aramid fiber ribs, carbon fiber ribs, or basalt fiber ribs can be installed inside the column body.

[0003] However, the existing technologies still have the following shortcomings: In existing solutions, the sound-absorbing material is laminated onto the column flange mainly by mechanical interlocking or physical bonding with cementitious materials. However, due to the extremely low water-cement ratio and large shrinkage of RPC, microcracks are easily generated at the interface due to shrinkage mismatch during service, leading to interface peeling or detachment between the sound-absorbing material and the column body, affecting the long-term safety and noise reduction effect of the sound barrier. Moreover, although RPC has high compressive strength, its tensile strength is relatively low and it is brittle. Under repeated dynamic loads such as wind loads and aerodynamic pulsation from train operation, tensile stress cracks are easily generated at the column flange. Summary of the Invention

[0004] To address the problems of interfacial delamination or detachment between the sound-absorbing material and the column body in existing technologies, and the tendency for tensile stress cracks to form at the column flange, this invention provides a manufacturing process for prestressed non-metallic sound barrier unit panels. This process utilizes a silane coupling agent as a "molecular bridge," with one end forming a strong Si-O-Si covalent bond with the silanol groups on the surface of the sound-absorbing material through hydrolysis and condensation reactions. The other end reacts with the active components (such as CSH gel) in the RPC matrix through its organic functional groups (such as amino and epoxy groups). This chemical bonding upgrades the interfacial bonding from physical interlocking to chemical bonding, fundamentally solving the interfacial delamination problem. By adding calcium sulfoaluminate expanding agent to the RPC, the volume expansion generated by its hydration to form ettringite is converted into pre-compression stress within the RPC under the constraint of the mold and inorganic fibers, effectively offsetting the tensile stress generated by shrinkage.

[0005] Specifically, this invention provides a manufacturing process for prestressed non-metallic sound barrier unit panels, including the following steps: S1. By weight, mix 100 parts cement, 15-25 parts mineral powder, 12-15 parts calcium sulfoaluminate expansion agent, 0.5-1.5 parts shrinkage reducer and 0.15-0.30 parts super absorbent polymer dry, then add 22-25 parts water wet mix, and finally add 250-300 parts inorganic fiber and stir to obtain active powder concrete. S2. Immerse the inorganic non-metallic sound-absorbing material in a silane coupling agent solution, remove it and dry it to obtain a surface-activated sound-absorbing material. S3. Place the surface-activated sound-absorbing material at the corresponding position on the flange of the column facing the sound source, and press it to form a sound-absorbing layer. S4. Pour the reactive powder concrete into the mold above the sound-absorbing layer, remove the mold, and then immerse the specimen in water for curing.

[0006] When cement comes into contact with water, it undergoes a hydration reaction, producing hydration products such as calcium silicate hydrate (CSH) gel and calcium hydroxide. CSH gel is the main source of RPC strength. At the same time, cement provides the alkaline environment and calcium source required for the hydration reaction of calcium sulfoaluminate expansive agent.

[0007] The core components of calcium sulfoaluminate expansion agent are anhydrous calcium sulfoaluminate and calcium oxide. During water curing, anhydrous calcium sulfoaluminate reacts with calcium hydroxide produced by cement hydration and calcium sulfate in the system to generate a large amount of hydrated ettringite, resulting in volume expansion. Under the combined action of the external constraint of the mold and the internal constraint of the fiber, the expansion force is converted into compressive stress inside the RPC, i.e., chemical prestress.

[0008] Shrinkage reducing agents reduce the surface tension of pore liquid by adsorbing at the solid-liquid interface, thereby reducing capillary shrinkage stress and reducing self-shrinkage from the source. Together with chemical prestress, they form a dual guarantee of "shrinkage reduction + crack resistance".

[0009] Superabsorbent polymers (RPCs) contain numerous hydrophilic groups (such as carboxyl and hydroxyl groups), enabling them to absorb and store several times their own weight in mixing water during the mixing process. Because RPCs have an extremely low water-cement ratio, the hydration reaction of cement and CSA expansive agents faces the risk of water shortage. SAP's "water storage-release" function ensures that the CSA expansive agent can fully react during water curing, allowing the chemical prestress to be fully established.

[0010] Regarding the interface issue, the silane coupling agent covalently connects the sound-absorbing material to the RPC matrix, upgrading the interfacial bonding from physical interlocking to chemical bonding. Regarding cracking, the hydration expansion of the CSA expansive agent, under constraint, is transformed into chemical prestress, actively counteracting the tensile stress caused by shrinkage and load from within. Regarding toughening, inorganic fibers provide bridging reinforcement.

[0011] Preferably, in S1, the raw materials are weighed in parts by weight as follows: 100 parts cement, 20 parts mineral powder, 12 parts calcium sulfoaluminate expansion agent, 1.0 part polyacrylate shrinkage reducer, and 0.20 parts sodium polyacrylate (SAP).

[0012] Preferably, 2-5 parts of redispersible latex powder are added during the dry mixing step, and water and 1-2 parts of nano-silica sol are mixed to obtain a mixture before wet mixing. The redispersible latex powder is uniformly mixed with the powder during the dry mixing stage, and a polymer film is formed after water is added. The active functional groups (such as carboxyl and hydroxyl groups) in this film react with the active groups grafted onto the silane coupling agent and interact with cement hydration products, forming a flexible "polymer bridge" at the interface, effectively buffering interfacial stress. The nano-silica sol is pre-dispersed in water before wet mixing, avoiding agglomeration during dry mixing. Its nanoparticles fill the interfacial micropores and provide a large number of silanol reaction sites. The two work together to form an organic-inorganic interpenetrating network, further enhancing the interfacial bonding strength.

[0013] Preferably, the shrinkage reducing agent is one or more of polyether shrinkage reducing agents, polyol shrinkage reducing agents, polycarboxylic acid shrinkage reducing agents, polyacrylate shrinkage reducing agents, or siloxane shrinkage reducing agents; the superabsorbent polymer is one or more of sodium polyacrylate, acrylic acid-acrylamide copolymer, polyacrylamide, or starch-based superabsorbent polymer.

[0014] Preferably, the inorganic fiber is one or more of basalt fiber, glass fiber, mineral wool fiber or ceramic fiber, and the length of the inorganic fiber is 6-18 mm and the diameter is 10-20 μm.

[0015] Preferably, the inorganic fibers described in S1 undergo pre-modification treatment before addition: the inorganic fibers are immersed in a composite modification solution containing 1.0%-2.0% nano-SiO2 dispersion and 0.3%-0.8% silane coupling agent, ultrasonically dispersed for 15-30 minutes, and then dried at 75-85℃. Before adding the RPC, the inorganic fibers are immersed in the composite modification solution of nano-SiO2 dispersion and silane coupling agent and ultrasonically dispersed. The nano-SiO2 particles adhere to the fiber surface, increasing surface roughness and the number of active sites, forming a synergistic modification effect with the silane coupling agent, significantly increasing the density of silanol grafting on the fiber surface. Ultrasonic dispersion ensures uniform coverage of the modifier. After this pre-modification, the chemical bonding and mechanical anchoring between the fiber and the RPC matrix are enhanced, significantly improving the fiber's reinforcement efficiency.

[0016] Preferably, the silane coupling agent solution in S2 is a 12% silane coupling agent ethanol solution, the soaking time is 20-40 minutes, the drying temperature is 75-85℃, and the drying time is 1-3 hours.

[0017] Preferably, in S4, the specimens are first cured in hot water or steam at 70-90℃ for 24-48 hours, and then transferred to water at 20±2℃ for 25-30 days. High-temperature conditions significantly accelerate the hydration reaction of cement, the reaction of mineral powder and pozzolanic material, and the hydration reaction rate of CSA expansive agent, enabling RPC to obtain most of its strength equivalent to 28 days of normal temperature curing within 48 hours. Simultaneously, high temperature promotes the hydrolysis and condensation reaction of silane coupling agent, allowing chemical prestress to be established earlier and the cross-linking reaction to be more complete. Furthermore, the humid and hot environment ensures the water supply required for the expansive agent reaction.

[0018] Preferably, before pouring the reactive powder concrete (RPC) in S4, a 0.5%-1.0% aqueous solution of silane coupling agent is uniformly sprayed onto the surface of the sound-absorbing layer as an interface transition layer, and allowed to stand for 10-15 minutes. This interface transition layer replenishes the local concentration of coupling agent at the interface, filling microscopic areas that the S2 soaking treatment may not have covered. The 10-15 minute standing time allows the coupling agent to fully penetrate the pores of the sound-absorbing material surface and hydrolyze, ensuring that sufficient coupling agent molecules participate in the cross-linking reaction at the interface during RPC pouring, thereby minimizing weak areas at the interface.

[0019] Preferably, before pouring the reactive powder concrete in S4, non-metallic prestressing tendons are pre-set in the mold at positions corresponding to the sound-absorbing layer. The surface of the non-metallic prestressing tendons is coated with a retarded epoxy resin coating. After pouring and curing in water for 3-7 days, the tendons are tensioned to 50%-60% of the design stress. The retarded epoxy resin coating prevents the bonding between the non-metallic prestressing tendons and the RPC in the early stage of pouring (the first 3-7 days), allowing the CSA expansion agent to fully hydrate and expand without being constrained by the non-metallic prestressing tendons during this period, and enabling the chemical prestress to be established preferentially. After the chemical prestress is basically established, the coating gradually becomes ineffective. At this time, the tendons are tensioned to 50%-60% of the design stress, so that the chemical prestress and mechanical prestress are superimposed rather than competing in time, and the two together construct a composite prestressing system.

[0020] Preferably, the non-metallic prestressing tendon is one of carbon fiber reinforced plastic tendon, aramid fiber reinforced plastic tendon, or basalt fiber reinforced plastic tendon.

[0021] The present invention has the following beneficial effects: This invention prepares reactive powder concrete by mixing cement, mineral powder, calcium sulfoaluminate expanding agent, shrinkage reducing agent, and superabsorbent polymer in a specific ratio. The superabsorbent polymer stores and slowly releases water in a low water-cement ratio system, providing sufficient water for the hydration of the calcium sulfoaluminate expanding agent. This allows the calcium sulfoaluminate expanding agent to continuously generate ettringite and undergo volume expansion during the water curing process. Constrained by the external mold and the internal inorganic fiber skeleton, this expansion is effectively converted into chemical prestress within the reactive powder concrete, fundamentally offsetting the tensile stress generated by self-shrinkage, drying shrinkage, and loads during RPC hardening and service, preventing cracking at the column flange. Simultaneously, the active groups grafted onto the surface of the sound-absorbing material with a silane coupling agent undergo a condensation reaction with the active components in the RPC matrix under water curing conditions, forming a three-dimensional chemical cross-linked network with Si-O-Si covalent bonds as the core. This reduces interfacial delamination problems, thereby significantly reducing the risk of cracking and improving flexural strength and impact toughness.

[0022] Other features and advantages of the invention will be set forth in the description which follows, and will be apparent in part from the description, or may be learned by practicing the invention. The objects and other advantages of the invention may be realized and obtained by means of the structures particularly pointed out in the written description and the accompanying drawings.

[0023] The technical solution of the present invention will be further described in detail below with reference to the accompanying drawings and embodiments. Attached Figure Description

[0024] The accompanying drawings are provided to further illustrate the invention and form part of the specification. They are used in conjunction with embodiments of the invention to explain the invention and do not constitute a limitation thereof. In the drawings: Figure 1 This is a flowchart illustrating the production process of a prestressed non-metallic sound barrier unit panel provided by the present invention. Detailed Implementation

[0025] The preferred embodiments of the present invention will be described below with reference to the accompanying drawings. It should be understood that the preferred embodiments described herein are for illustration and explanation only and are not intended to limit the present invention.

[0026] like Figure 1 As shown, the present invention provides a manufacturing process for prestressed non-metallic sound barrier unit panels, including the following steps: S1. By weight, mix 100 parts cement, 15-25 parts mineral powder, 12-15 parts calcium sulfoaluminate expansion agent, 0.5-1.5 parts shrinkage reducer and 0.15-0.30 parts super absorbent polymer dry, then add 22-25 parts water wet mix, and finally add 250-300 parts inorganic fiber and stir to obtain active powder concrete. S2. Immerse the inorganic non-metallic sound-absorbing material in a silane coupling agent solution, remove it and dry it to obtain a surface-activated sound-absorbing material. S3. Place the surface-activated sound-absorbing material at the corresponding position on the flange of the column facing the sound source, and press it to form a sound-absorbing layer. S4. Pour the reactive powder concrete into the mold above the sound-absorbing layer, remove the mold, and then immerse the specimen in water for curing.

[0027] The present invention will be further described below with reference to embodiments.

[0028] All raw materials used in the following examples are commercially available. The cement is ordinary silicate cement; the mineral powder is granulated blast furnace slag powder; the calcium sulfoaluminate expanding agent is a CSA type concrete expanding agent with an anhydrous calcium sulfoaluminate content of not less than 55%; the shrinkage reducing agent is a polyacrylate shrinkage reducing agent with a solid content of 40%; the super absorbent polymer is sodium polyacrylate-100 type water-absorbing resin with a particle size of 100-200 mesh; the inorganic fiber is basalt fiber with a length of 12 mm and a diameter of 13 μm; the inorganic non-metallic sound-absorbing material is open-pore perlite sound-absorbing board with a density of 250 kg / m³ and a thickness of 30 mm; the silane coupling agent is KH-550 type (γ-aminopropyltriethoxysilane) with a purity of ≥98%; the redispersible latex powder is ethylene-vinyl acetate copolymer type; and the nano silica sol is an aqueous dispersion with a solid content of 30% and a particle size of 10-20 nm.

[0029] Example 1

[0030] This embodiment provides a manufacturing process for a prestressed non-metallic sound barrier unit panel, including the following steps: S1: Weigh the raw materials according to the following parts by weight: 100 parts cement, 20 parts mineral powder, 12 parts calcium sulfoaluminate expanding agent, 1.0 part polyacrylate shrinkage reducing agent, and 0.20 parts sodium polyacrylate (SAP). Pour the above powders into a mixing pot and dry mix for 3 minutes to ensure that all components are fully mixed. Then add 23 parts water and wet mix for 3 minutes to allow the cement to begin hydration, the shrinkage reducing agent to be evenly dispersed in the liquid phase, and the SAP to absorb the mixing water to form an internal curing reservoir. Finally, add 280 parts basalt fiber and continue mixing for 9 minutes to ensure that the fiber is evenly dispersed in the slurry, thus obtaining active powder concrete.

[0031] S2: Immerse the perforated perlite sound-absorbing board in a 12% (volume percentage) KH-550 silane coupling agent ethanol solution for 30 minutes. After immersion, remove the board and dry it in an 80℃ oven for 2 hours. This allows the silane coupling agent to hydrolyze and undergo a dehydration condensation reaction with the silanol groups on the surface of the perlite to form Si-O-Si covalent bonds. This fixes one end of the coupling agent to the surface of the perlite while retaining the active amino group (-NH2) at the other end, thus obtaining a surface-activated sound-absorbing material.

[0032] S3: Place the surface-activated sound-absorbing material in the corresponding position on the flange facing the sound source in the H-shaped column mold, apply a pressure of 1.5KN to press and form, so that the sound-absorbing layer is accurately positioned and precisely sized, and the sound-absorbing layer is obtained.

[0033] S4: A 0.8% KH-550 silane coupling agent aqueous solution is uniformly sprayed onto the surface of the sound-absorbing layer as an interface transition layer. The mixture is allowed to stand for 12 minutes to allow the coupling agent to fully penetrate the pores of the sound-absorbing material surface and hydrolyze. The reactive powder concrete obtained in S1 is poured into a mold above the sound-absorbing layer and vibrated on a vibrating table for 4 minutes at a frequency of 50 Hz, allowing the RPC slurry to densely fill the mold cavity and partially penetrate the pores of the sound-absorbing material surface. After molding, the specimen is moved to a curing chamber and cured at 20±2℃ for 24 hours. The mold is then removed, and the specimen is immersed in water at 20±2℃ for another 28 days.

[0034] Example 2

[0035] This embodiment provides a production process for a prestressed non-metallic sound barrier unit panel, which differs from Embodiment 1 in that a crosslinking aid is added in S1.

[0036] S1: Weigh the raw materials by weight: 100 parts cement, 20 parts mineral powder, 12 parts calcium sulfoaluminate expanding agent, 1.0 part polyacrylate shrinkage reducing agent, 0.20 parts sodium polyacrylate (SAP), and 3 parts redispersible latex powder. Pour the above powders into a mixing pot and dry mix for 3 minutes to ensure thorough and uniform mixing. Pre-disperse 1.5 parts of nano-silica sol in 23 parts water to obtain a mixture, then add this mixture to the mixing pot and wet mix for 3 minutes. Finally, add 280 parts basalt fiber and continue mixing for 9 minutes to obtain active powder concrete.

[0037] S2 to S4 are the same as in Example 1.

[0038] Example 3

[0039] This embodiment provides a production process for a prestressed non-metallic sound barrier unit panel, which differs from Embodiment 2 in that the basalt fiber in S1 is pre-modified before being added.

[0040] S1: Basalt fibers are immersed in a composite modified liquid containing 1.5% nano-SiO2 dispersion and 0.5% KH-550 silane coupling agent, ultrasonically dispersed for 20 minutes, and then dried at 80℃ to obtain surface-modified basalt fibers.

[0041] Weigh the raw materials according to the following parts by weight: 100 parts cement, 20 parts mineral powder, 12 parts calcium sulfoaluminate expanding agent, 1.0 part polyacrylate shrinkage reducing agent, 0.20 parts sodium polyacrylate (SAP), and 3 parts redispersible latex powder. Pour the above powders into a mixing pot and dry mix for 3 minutes. Pre-disperse 1.5 parts of nano-silica sol in 23 parts water and add it to the mixing pot, then wet mix for 3 minutes. Finally, add 280 parts of pre-modified basalt fiber and continue mixing for 9 minutes to obtain reactive powder concrete.

[0042] S2 to S4 are the same as in Example 1.

[0043] Example 4

[0044] This embodiment provides a production process for a prestressed non-metallic sound barrier unit panel, which differs from Embodiment 2 in that the curing system in S4 is different.

[0045] S1 to S3 are the same as in Example 2.

[0046] S4: A 0.8% KH-550 silane coupling agent aqueous solution is uniformly sprayed onto the surface of the sound-absorbing layer as an interface transition layer, and allowed to stand for 12 minutes. Reactive powder concrete is poured into the mold above the sound-absorbing layer and vibrated on a vibrating table for 4 minutes at a frequency of 50 Hz. After molding, the specimen is moved into a steam curing chamber and cured in 80℃ steam for 48 hours. Then, the mold is removed, and the specimen is immersed in water at 20±2℃ for curing until the total age is 28 days.

[0047] Example 5

[0048] This embodiment provides a production process for a prestressed non-metallic sound barrier unit panel. The difference between this process and that of Embodiment 2 is that non-metallic prestressing tendons are pre-set and pre-tensioning is implemented before pouring the reactive powder concrete in S4.

[0049] S1 to S3 are the same as in Example 2.

[0050] S4: Carbon fiber reinforced plastic (CFRP) bars are pre-installed in the mold at positions corresponding to the sound-absorbing layer above. The surface of these CFRP bars is coated with a retarded epoxy resin coating. Reactive powder concrete is poured into the mold above the sound-absorbing layer and vibrated on a vibrating table for 4 minutes at a frequency of 50 Hz. After molding, the specimen is moved to a curing chamber and cured at 20±2℃ for 24 hours. The mold is then removed, and the specimen is immersed in water at 20±2℃ for 7 days to allow the CSA expanding agent to fully hydrate and the chemical prestress to be established. After 7 days, the CFRP bars are pre-tensioned to 55% of the design stress and locked in place. Curing continues in water at 20±2℃ for 28 days.

[0051] Comparative Example 1 This comparative example provides a manufacturing process for a non-metallic sound barrier unit panel, which differs from Example 1 in that: calcium sulfoaluminate expansion agent, shrinkage reducer, and highly absorbent polymer are not added, and the sound-absorbing material is not subjected to silane coupling agent surface activation treatment. The specific steps are as follows.

[0052] S1: Weigh the raw materials by weight: 100 parts cement and 20 parts mineral powder. Pour the above powder into a mixing pot and dry mix for 3 minutes. Add 23 parts water and wet mix for 3 minutes. Finally, add 280 parts basalt fiber and continue mixing for 9 minutes to obtain reactive powder concrete.

[0053] S2: Place the perforated perlite sound-absorbing board directly in the H-shaped column mold at the corresponding position on the flange facing the sound source, without any surface activation treatment, and apply 1.5KN pressure to form it.

[0054] S3: Pour the reactive powder concrete into the mold above the sound-absorbing layer and vibrate it on a vibrating table for 4 minutes at a frequency of 50 Hz. After molding, move the specimen into the curing room and cure it at 20±2℃ for 24 hours. Then remove the mold and cure it in water at 20±2℃ for 28 days.

[0055] Product performance testing The following performance tests were performed on the sound barrier unit panels prepared in Examples 1-5 and Comparative Examples 1-3: (1) Interface bonding strength: According to the test method of interface bonding strength in GB / T 9779-2015 "Multi-layer architectural coatings", a pull-out test was carried out at the interface between the sound-absorbing layer and RPC to test the interface bonding strength.

[0056] (2) Bending capacity: According to the bending strength test method in GB / T 15231-2023 "Test Method for Performance of Glass Fiber Reinforced Cement", the unit board was subjected to a four-point bending test to test its bending capacity.

[0057] (3) Shrinkage rate: The self-shrinkage rate of RPC specimens was tested in accordance with the non-contact shrinkage test method in GB / T 50082-2009 "Standard for Test Methods of Long-term Performance and Durability of Ordinary Concrete".

[0058] (4) Sound absorption coefficient: According to GB / T 18696.2-2002 "Measurement of sound absorption coefficient and acoustic impedance in acoustic impedance tubes - Part 2: Transfer function method", the sound absorption coefficient of the unit board was tested at frequencies of 500Hz and 1000Hz.

[0059] The test results are shown in Table 1.

[0060] Table 1 Performance test results of the examples and comparative examples

[0061] Results Analysis Table 1 shows that the interfacial bonding strength of Examples 1-5 is 3.2-4.1 MPa, while that of Comparative Example 1 (without any treatment) is only 1.4 MPa. This indicates that the surface activation treatment with the silane coupling agent increases the interfacial bonding strength from approximately 1.5 MPa (physical interlocking) to over 3.0 MPa. Example 3 (fiber pre-modification + crosslinking aid) reaches 4.1 MPa, which is the highest value.

[0062] The flexural bearing capacity of Examples 1-5 ranged from 42.5 to 51.6 kN, while that of Comparative Example 1 was only 28.3 kN. Example 5 (introducing non-metallic prestressing tendons) reached 51.6 kN, the highest value, indicating that the composite system of pre-tensioned mechanical prestressing and chemical prestressing has the optimal bearing capacity. Example 3 (fiber pre-modification) achieved 46.8 kN, which is better than Example 2 (44.1 kN) and Example 1 (42.5 kN), proving that fiber surface modification effectively improves the fiber reinforcement efficiency.

[0063] The self-shrinkage rate of Examples 1-5 The ratio 1 is as high as Example 4 (High-Temperature Steam Curing) is... The lowest value indicates that high-temperature curing promotes the full reaction of the expansion agent, enabling the chemical prestress to be established more completely.

[0064] The sound absorption coefficients of the various embodiments and comparative examples are basically the same (0.70-0.72 at 500Hz and 0.83-0.85 at 1000Hz), indicating that the surface activation treatment of the silane coupling agent and the spraying of the interface transition layer only chemically graft on the surface of the sound-absorbing material, without blocking the open pores inside the material, and the sound absorption performance is completely preserved.

[0065] Obviously, those skilled in the art can make various modifications and variations to this invention without departing from its spirit and scope. Therefore, if these modifications and variations fall within the scope of the claims of this invention and their equivalents, this invention also intends to include these modifications and variations.

Claims

1. A manufacturing process for prestressed non-metallic sound barrier unit panels, characterized in that, Includes the following steps: S1. By weight, mix 100 parts cement, 15-25 parts mineral powder, 12-15 parts calcium sulfoaluminate expansion agent, 0.5-1.5 parts shrinkage reducer and 0.15-0.30 parts super absorbent polymer dry, then add 22-25 parts water wet mix, and finally add 250-300 parts inorganic fiber and stir to obtain active powder concrete. S2. Immerse the inorganic non-metallic sound-absorbing material in a silane coupling agent solution, remove it and dry it to obtain a surface-activated sound-absorbing material. S3. Place the surface-activated sound-absorbing material at the corresponding position on the flange of the column facing the sound source, and press it to form a sound-absorbing layer. S4. Pour the reactive powder concrete into the mold above the sound-absorbing layer, remove the mold, and then immerse the specimen in water for curing.

2. The manufacturing process of prestressed non-metallic sound barrier unit panels according to claim 1, characterized in that, In the dry mixing step, 2-5 parts of redispersible latex powder are added. In the wet mixing step, water and 1-2 parts of nano silica sol are mixed to obtain a mixture, and then the mixture is added for wet mixing.

3. The manufacturing process of prestressed non-metallic sound barrier unit panels according to claim 1, characterized in that, The shrinkage reducing agent is one or more of polyether shrinkage reducing agents, polyol shrinkage reducing agents, polycarboxylic acid shrinkage reducing agents, polyacrylate shrinkage reducing agents, or siloxane shrinkage reducing agents; the superabsorbent polymer is one or more of sodium polyacrylate, acrylic acid-acrylamide copolymer, polyacrylamide, or starch-based superabsorbent polymer.

4. The manufacturing process of prestressed non-metallic sound barrier unit panels according to claim 1, characterized in that, The inorganic fiber is one or more of basalt fiber, glass fiber, mineral wool fiber or ceramic fiber, and the length of the inorganic fiber is 6-18 mm and the diameter is 10-20 μm.

5. The manufacturing process of prestressed non-metallic sound barrier unit panels according to claim 1, characterized in that, The inorganic fibers described in S1 are pre-modified before being added: the inorganic fibers are immersed in a composite modified liquid containing 1.0%-2.0% nano-SiO2 dispersion and 0.3%-0.8% silane coupling agent, ultrasonically dispersed for 15-30 minutes, and then dried at 75-85℃.

6. The manufacturing process of prestressed non-metallic sound barrier unit panels according to claim 1, characterized in that, The silane coupling agent solution mentioned in S2 is a 12% silane coupling agent ethanol solution, with a soaking time of 20-40 minutes, a drying temperature of 75-85℃, and a drying time of 1-3 hours.

7. The manufacturing process of prestressed non-metallic sound barrier unit panels according to claim 1, characterized in that, In S4, the specimens are first cured in hot water or steam at 70-90℃ for 24-48 hours, and then transferred to water at 20±2℃ for 25-30 days.

8. The manufacturing process of prestressed non-metallic sound barrier unit panels according to claim 1, characterized in that, Before pouring the active powder concrete in S4, a layer of 0.5%-1.0% silane coupling agent aqueous solution is uniformly sprayed onto the surface of the sound-absorbing layer as an interface transition layer, and left to stand for 10-15 minutes.

9. The manufacturing process of prestressed non-metallic sound barrier unit panels according to claim 1, characterized in that, Before pouring the active powder concrete in S4, non-metallic prestressing tendons are pre-set in the mold at the position corresponding to the sound-absorbing layer. The surface of the non-metallic prestressing tendons is coated with a retarding epoxy resin coating. After pouring and curing in water for 3-7 days, the tendons are tensioned to 50%-60% of the design stress.

10. The manufacturing process of prestressed non-metallic sound barrier unit panels according to claim 9, characterized in that, The non-metallic prestressing tendon is one of carbon fiber reinforced plastic tendon, aramid fiber reinforced plastic tendon, or basalt fiber reinforced plastic tendon.

Citation Information

Patent Citations

  • Sound barrier upright post and preparation method of sound barrier upright post

    CN104775369A